2011
DOI: 10.1152/ajpregu.00478.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glut4 is upregulated despite decreased insulin signaling during prolonged fasting in northern elephant seal pups

Abstract: Viscarra JA, Vázquez-Medina JP, Crocker DE, Ortiz RM. Glut4 is upregulated despite decreased insulin signaling during prolonged fasting in northern elephant seal pups. Am J Physiol Regul Integr Comp Physiol 300: R150 -R154, 2011. First published October 27, 2010 doi:10.1152/ajpregu.00478.2010.-Postprandial cellular glucose uptake is dependent on an insulin-signaling cascade in muscle and adipose tissue, resulting in the translocation of the insulindependent glucose transporter 4 (Glut4) into the plasma membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 40 publications
3
74
1
Order By: Relevance
“…Plasma HGPRT and XO activities increased (P<0.05) at each week across the fasting over the 7week measurement period (Fig.4C,D). cortisol, non-esterified fatty acids and promoting insulin resistance (Ortiz et al, 2000;Ortiz et al, 2001;Ortiz et al, 2003;Ortiz et al, 2006;Vázquez-Medina et al, 2010;Viscarra et al, 2011a;Viscarra et al, 2011b). Unfortunately, the molecular and physiological mechanisms adopted by seals to cope with prolonged fasting are not fully elucidated.…”
Section: Purine Metabolism Increases With Fastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma HGPRT and XO activities increased (P<0.05) at each week across the fasting over the 7week measurement period (Fig.4C,D). cortisol, non-esterified fatty acids and promoting insulin resistance (Ortiz et al, 2000;Ortiz et al, 2001;Ortiz et al, 2003;Ortiz et al, 2006;Vázquez-Medina et al, 2010;Viscarra et al, 2011a;Viscarra et al, 2011b). Unfortunately, the molecular and physiological mechanisms adopted by seals to cope with prolonged fasting are not fully elucidated.…”
Section: Purine Metabolism Increases With Fastingmentioning
confidence: 99%
“…In humans, rats and mice, prolonged fasting increases oxidant production, oxidative damage and inflammation (Crescimanno et al, 1989;Di Simplicio et al, 1997;Grattagliano et al, 2000;Kondoh et al, 2003;Mårtensson, 1986;Sorensen et al, 2006;Souza Rocha et al, 2008;Wu et al, 2004). In elephant seals, prolonged fasting does not induce oxidative damage or inflammation despite promoting the chronic activation of the renin-angiotensin system (RAS) and increasing circulating cortisol, NADPH oxidase activity, Nox4 protein expression and insulin resistance (Ortiz et al, 2000;Ortiz et al, 2002;Vázquez-Medina et al, 2010;Viscarra et al, 2011a;Viscarra et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…For the maintenance of circulating glucose levels, fasting pups rely on lipid oxidation and efficient glucose recycling (Champagne et al, 2005;Champagne et al, 2012;Costa and Ortiz, 1982;Tavoni et al, 2013), coupled with insulin resistance (IR)-like conditions (Fowler et al, 2008;Viscarra et al, 2011a;Viscarra et al, 2011b). These adapted mechanisms allow pups to meet their energetic burdens during prolonged fasting.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, males have low rates of water flux and spare protein efficiently (Ortiz et al, 2006;Crocker et al, 2012). Studies in fasting and lactating female elephant seals have suggested reduced insulin response and sensitivity (Fowler et al, 2008;Viscarra et al, 2011aViscarra et al, , 2011b. To date, no studies have examined the hormone regulation of metabolism in adult male pinnipeds during natural breeding fasts.…”
Section: Introductionmentioning
confidence: 99%